2018
DOI: 10.21873/cgp.20088
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Heterogeneously-methylated DNA Fragments Using Epiallele-sensitive Droplet Digital Polymerase Chain Reaction (EAST-ddPCR)

Abstract: All individual heterogeneously-methylated epialleles were quantifiable by a set of fluorescence-labeled probes with complementary sequences to epialleles in a closed-tube and high-throughput manner. The new method named epiallele-sensitive droplet digital PCR (EAST-ddPCR) may give new insights in the generation and regulation of epialleles and may help in finding new biomarkers for the diagnosis of benign und malignant diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The FAM-positive signals that were detected in control sample 3 (C3) are characterized by a significantly lower signal amplitude compared to that of patient samples (Figure 6B ). The presence of the FAM-positive signals can be explained by the occurrence of heterogeneous methylated epialleles as recently demonstrated for the PLA2R1 gene [ 39 ], although at a reasonably low level. The results of this proof-of-principle study are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The FAM-positive signals that were detected in control sample 3 (C3) are characterized by a significantly lower signal amplitude compared to that of patient samples (Figure 6B ). The presence of the FAM-positive signals can be explained by the occurrence of heterogeneous methylated epialleles as recently demonstrated for the PLA2R1 gene [ 39 ], although at a reasonably low level. The results of this proof-of-principle study are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 67%
“…To assess the analytical sensitivity's reliance on the primer design, MgCl 2 concentration, and annealing temperature, two sets of standard DNA samples were prepared and contained at first 25,000 copies of unmethylated PLA2R1 -DNA along with 0, 5, 9, 18, 94, 375, 750, and 3,000 copies of methylated PLA2R1 -DNA from U937 cells. In previous studies we identified the PLA2R1 promoter hypermethylated in U937 leukemic cell lines and in LNCaP prostate cancer cell line [ 35 , 38 , 39 ]. As the PLA2R1 promoter was completely methylated in every DNA isolation independent on the used passages of U937 cells and the DNA methylation degree of the PLA2R1 promoter in LNCaP cells varied between passages in a range of 83-95% we decided to use U937 DNA as model target of methylated tumor DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The widest application of ddPCR in cancer is for the detection of oncogenic mutations in circulating tumor cells or cell-free tumor DNA [ 17 ]. New applications, however, have emerged to assess the level of intra-tumoral heterogeneity [ 18 ]. For this work, we aimed to use ddPCR to determine in a tumor sample how many cells presented HER2 co-amplified with another HER member.…”
Section: Resultsmentioning
confidence: 99%
“…Massively parallel deep sequencing is an exact research technique, but it is high-cost and complex [ 50 , 51 ]. Denaturing Gradient Gel Electrophoresis can visualize heterogeneous methylation [ 52 , 53 ], droplet digital PCR (ddPCR) can be used to identify and quantify heterogeneously methylated epialleles as a new technique [ 21 ], and EpiHRMAssay can provide additional information for assessing heterogeneous methylation [ 54 ]. But these techniques are expensive and have not been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…More so, because the methylation of individual CpG sites is not faithfully maintained by DNA methyltransferase [ 17 ], the methylation of alleles is incomplete and could reflect epigenetic instability [ 18 ]. To date, studies on the relationship between heterogeneous methylation and tumorigenesis [ 17 – 21 ] demonstrated that heterogeneous methylation might appear early in the progression of the tumor [ 19 ] and correlate with gene silencing. It has been proved that age [ 22 ], environmental factors [ 23 25 ], cell division [ 26 ], and other cancer-associated phenomena [ 27 , 28 ] are contributing factors in the development of heterogeneous methylation.…”
Section: Introductionmentioning
confidence: 99%